Isytiqaq, Taraduf, Isytirok, dan Tadladh: Pilar-Pilar Semantik dalam Bahasa Arab Klasik - Ainur Rofiq Sofa; Holifatul Munawaroh (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
. This article explores four foundational pillars of Arabic semantics: Isytiqaq (derivation), Taraduf (synonymy), Isytirok (polysemy), and Tadladh (antonymy). These concepts are crucial for understanding the dynamic and layered nature of meaning in classical Arabic texts, including the Qur'an, Hadith, and classical Arabic literature. Isytiqaq provides insight into the origin and development of words through their root structures, while Taraduf illustrates the richness of Arabic vocabulary through synonymous expressions. Isytirok addresses the phenomenon of a single word carrying multiple meanings based on context, and Tadladh reveals semantic oppositions that enhance rhetorical expression and textual clarity. This study emphasizes the importance of these four semantic pillars in linguistic analysis and interpretation, highlighting their role in the beauty and precision of the Arabic language.